The Mediation Impact of Contingent Workforce in the Connection between Organizational Commitment and Job Satisfaction - P, Nagaraja (International Journal of Multidisciplinary: Applied Business and Education Research, 2020)
Most recently there has been wonderful development in the market for a temporary, or contingent, labor power in the United States. The total labor market during 10 years amid somewhere in the range of 1986 and 1996 developed by 1.7 percent, in a similar period, work in contingent services became 10.3 percent. Among the technical, pro-fessional, and managerial category of contingent workforce, there is a rapid growth of payroll noticed. Contingence workforce continues to thrive in Asian countries too. India is no exceptional from this view-point hence this has made the purpose of the present research paper to contribute the brief and clear insights towards contingent work-force, organizational commitment, and job satisfaction. The present paper is an empirical evidence for the mediation effect of contingent workforce in the relationship between organizational commitment and job satisfaction. This is a survey-based research work carried out to explore the subject of temporary workforce in Indian context. A sample of 284 respondents were participated in the survey and the typical fining from the present study is contingent workforce fully mediates the relationship between organizational commitment and job satisfaction. Partial Least Square based Structural Equation Mod-elling was used to test the proposed hypotheses.